Screening of Aroma Compounds in Commercial Tea (Camellia sinensis) from Indonesia and Testing Their Activity as Antioxidants - Warsito, Warsito; Alief, M. Fadel; Azzahra, Vina Octavia; Rahman, M. Farid; Retnowati, Rurini (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
Tea from tea leaves of the Camellia sinensis species is a superior industrial plant that promises superior bioactivity. For a more in-depth study of the essential oils contained in commercial teas on the market, their significant characteristic from their constituent compounds were determined. The essential oil yields of the three commercial samples were obtained by distillation using a Liken-Nickerson vessel and analyzed by gas chromatography-mass spectrometry (GC-MS), then tested for antioxidant properties by the DPPH method. The yield obtained ranged from 0.08-0.13%. The main major components (more than 0.5% identified) contained in the three samples identified were benzyl acetate, between 4,56-26.27%, and linalool compounds from tea leaves, as much as 20.59%, and 3.42% in samples C and B which were not found in sample A. As shown by our results, antioxidant activity significantly correlated with benzyl acetate and linalool composition. Sample A showed the best antioxidant profile, with highest inhibition (IC50 20.19 mg/mL).